Peningkatan Kesiapan Kerja Lulusan melalui Pelatihan Literasi Keuangan dan Spirit Etos Budaya Kerja Jepang di SMK - Hendrike Priventa; Umi Handayani; Ricky Darmawan; Kustiyono Kustiyono; Izza Aulia; AL Thoriq Muhamad Hugo (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program aims to enhance the job readiness of Vocational High School (SMK) students through financial literacy training and the strengthening of the spirit of Japanese work culture. The main problems faced by the partner school include students’ low understanding of personal financial management and the limited internalization of work ethic values relevant to the demands of modern industries. The training was conducted through interactive lectures, case studies, simulations, and group discussions. The financial literacy materials focused on income management, financial planning, saving, and consumption control. Meanwhile, the Japanese work ethic materials emphasized discipline, responsibility, hard work, kaizen (continuous improvement), and teamwork. The evaluation results indicate a significant improvement in students’ understanding of financial literacy principles, as well as positive changes in their attitudes toward productive work ethics. In addition, students showed increased motivation to apply these values as they prepare to enter the industrial workforce. This program has proven effective in strengthening students’ non-technical competencies, making them better prepared to face the challenges of the working world.